Data from: Deep sequencing of the olfactory epithelium reveals specific chemosensory receptors are expressed at sexual maturity in the European eel Anguilla anguilla - Churcher, Allison M.; Hubbard, Peter C.; Marques, João P.; Canário, Adelino V. M.; Huertas, Mar (Data Archiving and Networked Services (DANS), 2019)
Vertebrate genomes encode a diversity of G protein-coupled receptors (GPCR) that belong to large gene families and are used by olfactory systems to detect chemical cues found in the environment. It is not clear however, if individual receptors from these large gene families have evolved roles that are specific to certain life stages. Here, we used deep sequencing to identify differentially expressed receptor transcripts in the olfactory epithelia (OE) of freshwater, seawater and sexually mature male eels (Anguilla anguilla). This species is particularly intriguing because of its complex life cycle, extreme long distance migrations and early-branching position within the teleost phylogeny. In the A. anguilla OE, we identified full-length transcripts for 13, 112, 6 and 38 trace-amine associated receptors (TAAR), odorant receptors (OR) and type I and type II vomeronasal receptors (V1R and V2R). Most of these receptors were expressed at similar levels at different life stages and that a subset of OR and V2R-like transcripts were more abundant in sexually mature males suggesting that ORs and V2R-like genes are important for reproduction. We also identified a set of GPCR signal transduction genes that were differentially expressed indicating that eels make use of different GPCR signal transduction genes at different life stages. The finding that a diversity of chemosensory receptors are expressed in the olfactory epithelium and that a subset are differentially expressed suggest that most receptors belonging to large chemosensory gene families have functions that are important at multiple life stages while a subset have evolved specific functions at different life stages. Aanguilla olfactory epithelium transcriptome assemblyThis is the Trinity assembled olfactory epithelium transcriptome (Illiumna HiSeq 2000) for Anguilla anguilla.Aanguilla_olfactory_epithelium_transcriptome_assembly.fastaAanguilla_olfactory_expression_dataThese are the expression data for the olfactory epithelium of freshwater (FW), seawater (SW) and ...